The genomics of mimicry: Gene expression throughout development provides insights into convergent and divergent phenotypes in a Müllerian mimicry system - Adam M. M. Stuckert; Mathieu Chouteau; Melanie McClure; Troy M. LaPolice; Tyler Linderoth; Rasmus Nielsen; Kyle Summers; Matthew D. MacManes (Molecular Ecology, 2024)
A common goal in evolutionary biology is to discern the mechanisms that produce the astounding diversity of morphologies seen across the tree of life. Aposematic species, those with a conspicuous phenotype coupled with some form of defence, are excellent models to understand the link between vivid colour pattern variations, the natural selection shaping it, and the underlying genetic mechanisms underpinning this variation. Mimicry systems in which species share a conspicuous phenotype can provide an even better model for understanding the mechanisms of colour production in aposematic species, especially if comimics have divergent evolutionary histories. Here we investigate the genetic mechanisms by which mimicry is produced in poison frogs. We assembled a 6.02‐Gbp genome with a contig N50 of 310 Kbp, a scaffold N50 of 390 Kbp and 85% of expected tetrapod genes. We leveraged this genome to conduct gene expression analyses throughout development of four colour morphs of Ranitomeya imitator and two colour morphs from both R. fantastica and R. variabilis which R. imitator mimics. We identified a large number of pigmentation and patterning genes differentially expressed throughout development, many of them related to melanophores/melanin, iridophore development and guanine synthesis. We also identify the pteridine synthesis pathway (including genes such as qdpr and xdh ) as a key driver of the variation in colour between morphs of these species, and identify several plausible candidates for colouration in vertebrates (e.g. cd36 , ep‐cadherin and perlwapin ). Finally, we hypothesise that keratin genes (e.g. krt8 ) are important for producing different structural colours within these frogs.

A holobiont view of island biogeography: Unravelling patterns driving the nascent diversification of a Hawaiian spider and its microbial associates - Ellie E. Armstrong; Benoît Perez‐Lamarque; Ke Bi; Cerise Chen; Leontine E. Becking; Jun Ying Lim; Tyler Linderoth; Henrik Krehenwinkel; Rosemary G. Gillespie (Molecular Ecology, 2022)
The diversification of a host lineage can be influenced by both the external environment and its assemblage of microbes. Here, we use a young lineage of spiders, distributed along a chronologically arranged series of volcanic mountains, to investigate how their associated microbial communities have changed as the spiders colonized new locations. Using the stick spider Ariamnes waikula (Araneae, Theridiidae) on the island of Hawaiʻi, and outgroup taxa on older islands, we tested whether each component of the “holobiont” (spider hosts, intracellular endosymbionts and gut microbial communities) showed correlated signatures of diversity due to sequential colonization from older to younger volcanoes. To investigate this, we generated ddRAD data for the host spiders and 16S rRNA gene amplicon data from their microbiota. We expected sequential colonizations to result in a (phylo)genetic structuring of the host spiders and in a diversity gradient in microbial communities. The results showed that the host A . waikula is indeed structured by geographical isolation, suggesting sequential colonization from older to younger volcanoes. Similarly, the endosymbiont communities were markedly different between Ariamnes species on different islands, but more homogeneous among A . waikula populations on the island of Hawaiʻi. Conversely, the gut microbiota, which we suspect is generally environmentally derived, was largely conserved across all populations and species. Our results show that different components of the holobiont respond in distinct ways to the dynamic environment of the volcanic archipelago. This highlights the necessity of understanding the interplay between different components of the holobiont, to properly characterize its evolution.

RETRACTED: The genomics of mimicry: Gene expression throughout development provides insights into convergent and divergent phenotypes in a Müllerian mimicry system - Adam M. M. Stuckert; Mathieu Chouteau; Melanie McClure; Troy M. LaPolice; Tyler Linderoth; Rasmus Nielsen; Kyle Summers; Matthew D. MacManes (Molecular Ecology, 2021)
A common goal in evolutionary biology is to discern the mechanisms that produce the astounding diversity of morphologies seen across the tree of life. Aposematic species, those with a conspicuous phenotype coupled with some form of defence, are excellent models to understand the link between vivid colour pattern variations, the natural selection shaping it, and the underlying genetic mechanisms underpinning this variation. Mimicry systems in which multiple species share the same conspicuous phenotype can provide an even better model for understanding the mechanisms of colour production in aposematic species, especially if comimics have divergent evolutionary histories. Here we investigate the genetic mechanisms by which vivid colour and pattern are produced in a Müllerian mimicry complex of poison frogs. We did this by first assembling a high‐quality de novo genome assembly for the mimic poison frog Ranitomeya imitator . This assembled genome is 6.8 Gbp in size, with a contig N50 of 300 Kbp R . imitator and two colour morphs from both Ranitomeya fantastica and R . variabilis which R . imitator mimics. We identified a large number of pigmentation and patterning genes that are differentially expressed throughout development, many of them related to melanocyte development, melanin synthesis, iridophore development and guanine synthesis. Polytypic differences within species may be the result of differences in expression and/or timing of expression, whereas convergence for colour pattern between species does not appear to be due to the same changes in gene expression. In addition, we identify the pteridine synthesis pathway (including genes such as qdpr and xdh ) as a key driver of the variation in colour between morphs of these species. Finally, we hypothesize that genes in the keratin family are important for producing different structural colours within these frogs.

Divergence, gene flow, and the origin of leapfrog geographic distributions: The history of colour pattern variation in Phyllobates poison‐dart frogs - Roberto Márquez; Tyler P. Linderoth; Daniel Mejía‐Vargas; Rasmus Nielsen; Adolfo Amézquita; Marcus R. Kronforst (Molecular Ecology, 2020)
The geographic distribution of phenotypic variation among closely related populations is a valuable source of information about the evolutionary processes that generate and maintain biodiversity. Leapfrog distributions, in which phenotypically similar populations are disjunctly distributed and separated by one or more phenotypically distinct populations, represent geographic replicates for the existence of a phenotype, and are therefore especially informative. These geographic patterns have mostly been studied from phylogenetic perspectives to understand how common ancestry and divergent evolution drive their formation. Other processes, such as gene flow between populations, have not received as much attention. Here, we investigate the roles of divergence and gene flow between populations in the origin and maintenance of a leapfrog distribution in Phyllobates poison frogs. We found evidence for high levels of gene flow between neighbouring populations but not over long distances, indicating that gene flow between populations exhibiting the central phenotype may have a homogenizing effect that maintains their similarity, and that introgression between ‘leapfroging’ taxa has not played a prominent role as a driver of phenotypic diversity in Phyllobates . Although phylogenetic analyses suggest that the leapfrog distribution was formed through independent evolution of the peripheral (i.e. leapfrogging) populations, the elevated levels of gene flow between geographically close populations poise alternative scenarios, such as the history of phenotypic change becoming decoupled from genome‐averaged patterns of divergence, which we cannot rule out. These results highlight the importance of incorporating gene flow between populations into the study of geographic variation in phenotypes, both as a driver of phenotypic diversity and as a confounding factor of phylogeographic inferences.

Unlocking the vault: next‐generation museum population genomics - Ke Bi; Tyler Linderoth; Dan Vanderpool; Jeffrey M. Good; Rasmus Nielsen; Craig Moritz (Molecular Ecology, 2013)
Natural history museum collections provide unique resources for understanding how species respond to environmental change, including the abrupt, anthropogenic climate change of the past century. Ideally, researchers would conduct genome‐scale screening of museum specimens to explore the evolutionary consequences of environmental changes, but to date such analyses have been severely limited by the numerous challenges of working with the highly degraded DNA typical of historic samples. Here, we circumvent these challenges by using custom, multiplexed, exon capture to enrich and sequence ~11 000 exons (~4 Mb) from early 20th‐century museum skins. We used this approach to test for changes in genomic diversity accompanying a climate‐related range retraction in the alpine chipmunks ( T amias alpinus ) in the high Sierra Nevada area of California, USA . We developed robust bioinformatic pipelines that rigorously detect and filter out base misincorporations in DNA derived from skins, most of which likely resulted from postmortem damage. Furthermore, to accommodate genotyping uncertainties associated with low‐medium coverage data, we applied a recently developed probabilistic method to call single‐nucleotide polymorphisms and estimate allele frequencies and the joint site frequency spectrum. Our results show increased genetic subdivision following range retraction, but no change in overall genetic diversity at either nonsynonymous or synonymous sites. This case study showcases the advantages of integrating emerging genomic and statistical tools in museum collection‐based population genomic applications. Such technical advances greatly enhance the value of museum collections, even where a pre‐existing reference is lacking and points to a broad range of potential applications in evolutionary and conservation biology.